2022
DOI: 10.3389/fnins.2022.998932
|View full text |Cite
|
Sign up to set email alerts
|

The role of neurotransmitter systems in mediating deep brain stimulation effects in Parkinson’s disease

Abstract: Deep brain stimulation (DBS) is among the most successful paradigms in both translational and reverse translational neuroscience. DBS has developed into a standard treatment for movement disorders such as Parkinson’s disease (PD) in recent decades, however, specific mechanisms behind DBS’s efficacy and side effects remain unrevealed. Several hypotheses have been proposed, including neuronal firing rate and pattern theories that emphasize the impact of DBS on local circuitry but detail distant electrophysiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 186 publications
1
7
0
Order By: Relevance
“…However, magnetoelectric stimulation did not show a significant difference in the co-expression of ChAT/c-Fos cells in the PPN. Those histological and behavioral findings are somewhat similar to the known effects of high frequency STN-DBS [21].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, magnetoelectric stimulation did not show a significant difference in the co-expression of ChAT/c-Fos cells in the PPN. Those histological and behavioral findings are somewhat similar to the known effects of high frequency STN-DBS [21].…”
Section: Discussionsupporting
confidence: 83%
“…Clarifying whether this approach induces similar changes in the brain could help establish magnetoelectric DBS as a suitable alternative to conventional DBS. In PD research, subthalamic nucleus (STN)-DBS has been shown to alter the activity of dopaminergic, serotonergic, and cholinergic systems in the ventral tegmental area (VTA) and substantia nigra pars compacta (SNc), dorsal raphe nucleus (DRN), and pedunculopontine nucleus (PPN) both in healthy and PD conditions [17][18][19][20]; reviewed in [21].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the inhibitory role of IFG in motor control ( Kenner et al, 2010 ; Rae et al, 2015 ; Aron et al, 2016 ; Chen et al, 2020 ), it is possible that the abnormal IFG over-excitability found in the OFF mode reflects excessive inhibitory inputs coming from the IFG to M1. STN-DBS has been shown to trigger GABA modulation in the basal ganglia and thalamus ( Stefani et al, 2011 ; Buchanan et al, 2014 ; Alosaimi et al, 2022 ). Our results suggest that clinically efficient STN-DBS might also partially exert its beneficial effects through a transient GABAergic disinhibition propagating to the cortex.…”
Section: Discussionmentioning
confidence: 99%
“…An exploratory grid of 5×5 targets spaced by 7 mm centered on the anatomical hotspot was used. Once the experimenter found the hotspot, defined as the point eliciting the most reliable and the highest MEP, the resting motor threshold (rMT) was assessed using TMSMTAT ( Awiszus, 2011 ). The first experimental stimulation condition was then set (DBS ON or OFF) and the TMS-EMG motor mapping began.…”
Section: Methodsmentioning
confidence: 99%
“…Neurotechnology already has the potential to alter the brain's chemistry and future developments predict that it will soon be able to create new neural connections between different parts of the nervous system ( 23 ). This will have huge therapeutic benefits for people with a range of neurological conditions, for example, stroke, chronic pain, paralysis, or psychological disorders, including anxiety and post-traumatic stress disorder.…”
Section: What Does the Rise Of Neurotechnology Mean For The Future Of...mentioning
confidence: 99%